Membangun Pengelolaan Keuangan dan Entrepreneur Santri di Masa Pandemi Covid Guna Meningkatkan Kemandirian Pondok Pesantren Al - Istiqomah Desa Telaga Waru Kecamatan Labuapi Kabupaten Lombok Barat - Hermanto Hermanto; Thatok Asmony; Prayitno Basuki (Jurnal Gema Ngabdi, 2021)
This counseling and training activity on building financial management and student entrepreneurs during the COVID-19 pandemic in order to increase the independence of the Al-Istiqomah Islamic boarding school in Telaga Waru Village, Labuapi District, West Lombok Regency, aims to provide understanding and training to boarding school administrators and students in West Lombok Regency. . In addition, this training was carried out to provide knowledge to Islamic boarding school administrators and students about the importance of making financial reports and entrepreneurship education during the covid-19 pandemic so that funds from donors can be managed properly and can be managed in the field of entrepreneurship in order to increase the independence of Islamic boarding schools. . In the end, this activity is expected to produce human resources who are able to manage finances and the talents of students in the field of entrepreneurship. This training activity will be aimed at the management of the Al - Istiqomah Islamic Boarding School in Telaga Waru Village, Labuapi District, West Lombok Regency. The implementation of the activity is carried out with an approach to providing material that is relevant to the needs of Islamic boarding school administrators according to PSAK 45 and procedures for building student entrepreneurs during the pandemic. Another hope is that this activity can be a means to carry out community service activities, in particular providing counseling and training on the preparation of financial reports as well as training on building student entrepreneurs during the COVID-19 pandemic.